Meningkatkan Ketrampilan Lulusan melalui Pengembangan Kurikulum Pastoral Konseling Berdasarkan Merdeka Belajar dan Kampus Merdeka dalam Kegiatan Magang di Institut Agama Kristen Negeri Tarutung - Malau, Oloria; Sihombing, Robinhot; Sitompul, Sabar Rudi; Sipahutar, Melina Agustina (JURNAL TERUNA BHAKTI, 2022)
In accordance with the current independent learning program and independent campus, especially in the implementation of internships/work practices, the existing Pastoral Counseling study program curriculum has the potential to be developed. In order to achieve graduates of the IAKN Tarutung Pastoral Counseling Study Program who are skilled in mentoring in accordance with the expectations of the achievement of the graduate profile and able to achieve the IAKN Tarutung mission. The purpose of this research is to develop a Pastoral Counseling Curriculum based on the Independent Learning and Independent Campus in Internship/Work Practice activities. This article uses research and development (R&D) methods. Referring to the results of the Curriculum expert validator regarding the development of the Pastoral Counseling study program curriculum based on the Merdeka Learning Independent Campus in the internship/work practice at the Faculty of Theological Sciences, IAKN Tarutung, it was concluded that it is suitable for use in learning Pastoral Counseling study programs with eligibility criteria levels 85, 96 %. Likewise, based on the results of the assessment of Pastoral Counseling expert validators/internship partners in terms of curriculum development research, it was concluded that it was suitable for use in Pastoral Counseling study program learning with a level of eligibility criteria of 85, 67%. With the conclusion that the curriculum development presented in this study is feasible to use and "does not need to be revised". AbstrakSesuai dengan program Merdeka Belajar dan Kampus Merdeka saat ini, khususnya dalam pelaksanaan magang/praktik kerja, kurikulum program studi Konseling Pastoral yang ada sangat potensial untuk dikembangkan. Dalam rangka mewujudkan lulusan Program Studi Konseling Pastoral IAKN Tarutung yang terampil dalam pendampingan sesuai dengan harapan pencapaian pro-fil lulusan, serta mampu mencapai misi IAKN Tarutung. Tujuan penelitian ini adalah untuk mengem-bangkan Kurikulum Konseling Pastoral berbasis Merdeka Belajar dan Kampus Merdeka dalam kegiatan Magang/Praktik. Artikel ini menggunakan metode penelitian dan pengembangan (R&D). Merujuk pada hasil validator ahli Kurikulum mengenai pengembangan kurikulum program studi Konseling Pastoral berbasis Kampus Mandiri Belajar Merdeka pada magang/praktik kerja di Fakultas Ilmu Teologi IAKN Tarutung, maka disimpulkan layak digunakan dalam pembelajaran program studi Konseling Pastoral dengan tingkat kriteria kelayakan 85,96%. Demikian juga berdasarkan hasil penilaian validator ahli Konseling Pastoral/mitra magang ditinjau dari penelitian pengembangan kurikulum, disimpulkan layak digunakan dalam pembelajaran program studi Konseling Pastoral dengan tingkat kriteria kelayakan 85,67%. Dengan kesimpulan bahwa pengembangan kurikulum yang disajikan dalam penelitian ini layak digunakan dan “tidak perlu direvisi”.